DIGITALIZATION OF THE FINANCIAL AND ECONOMIC SPHERE IN UKRAINE: STATUS AND PROSPECTS OF DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2022)
One of the key trends in the progressive development of the modern economy and the world economy as a whole is digitalization. With the accelerated development of digital technologies, the formation of a digital society, digitalization is constantly under the influence of growing socio-economic needs, blocks access to the resources of the global information network, the Internet opens up new opportunities. Therefore, the trend towards the importance of the digital economy, which is a new valuable entity, becomes obvious.The subject of the study is the possibilities and main threats of modern digitalization. The purpose of the article is to analyze the current state of development of the digital economy, its opportunities and main threats in accordance with world trends and to develop proposals for its further development. Task: research on the number of Internet users, opportunities and threats and problems related to digitalization for all segments of the population in connection with the growing role of computerization in the global dimension.In the process of this research, such scientific methods as: system analysis, comparative analysis and generalization method were used. The following results were obtained: the analysis of opportunities and main threats of digitalization indicates the dynamic development of digitalization in the world. It has been studied that the high speed of digitization of all aspects of life is due, first of all, to its possible positive manifestations and consequences at all levels. It has been established that digitalization is a promising direction of both scientific research and practical orientation, because it is the digital economy that acts as the basis for the development of effective state administration, economy, business-environment, social sphere and the whole society.Conclusions: in order for the benefits of the digital economy to be fully manifested, their balanced development is needed, the removal of barriers to digital transformations must be done through the combined efforts of all branches of government, business and the public.
Keywords: digitization, digitalization, economy, finance, innovative technologies